UPAYA PELAYANAN KESEHATAN BAGI MASYARAKAT DI DESA SILAU DUNIA DALAM RANGKA KEGIATAN PENGABDIAN MASYARAKAT - Ummi Nur Afinni Dwi Jayanti; Siti Rodiyah; Hanifah Dinda Difanie Simanjuntak; Halimatussya'diyah Hasibuan; Masdelina Sipahutar; Merliyana Saragih (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Health problems can be caused by the emergence of diseases in the human body as a result of bad daily life habits or can also be caused by hereditary diseases (genes). One type of disease that is commonly experienced by people in Indonesia is high blood pressure and diabetes. The lack of awareness to maintain the health of the people who live in rural areas is one of the factors causing the high number of sufferers of both types of disease every year. The purpose of this activity is to provide education in the form of efforts to increase public awareness of hypertension and diabetes mellitus as well as health services for the community in the form of checking blood pressure and diabetes mellitus. The method in this activity is in the form of a lecture method followed by direct activities in the form of health services to the community. From this activity, it was found that the community seemed enthusiastic about attending this activity and happy with the services provided, for that it is hoped that the people in Desa Silau Dunia can increase their concern for health through the activities that have been carried out.